Analytical Study on Marital Conflict among Occupational Couples and Its Impact on Their Marital Life: Exploring the Impact of Dual Careers on Marital Conflict and Satisfaction (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper tries to examine the inescapable disagreements among urban married couples while carring the obligations of marriagehome and driven careers, prompting exceptionally stressful lives. In particular, the present paper investigates the propensity among dual career couples to express their disagreements straightforwardly to one another, and the issues that trigger such contentions. The recent trends of urbanization have affected the customary ideas of roles and responsibilities in families. Improved chances of training for ladies and their resulting section into formal occupations as experts have explicitly modified the traditional role expectations and the structure of families. In recent years, the exceptional weight of assuming the profoundly fighting circles of both home and work is causing tangible stress on the couples. The interface among work and home is perceptible, particularly for dual career couples, attributable to the high duty and obligation that every one of these domains entails.